Chinese police cadets’ attitudes toward domestic violence: a pretest/posttest design - Hayes, Brittany (Crime & delinquency, 2022)
Since the Domestic Violence (DV) Law was passed in China in 2015, knowledge of this mandate has been relatively unexplored. Data from 401 police cadets attending Zhejiang Police College in Hangzhou, China, are analyzed. A pretest/posttest design was used to assess changes in attitudes toward DV after a 30-minute lecture on DV. The influence of gender, whether the cadet views DV as a priority for law enforcement, and knowledge of services are examined. Findings demonstrate the utility of the training while recognizing cadets with prior knowledge of DV may have resisted the training. Given entrance into law enforcement is more likely for individuals who attend a police college in China, implications include incorporating a DV course at police colleges.